KRITIK SOSIAL PADA DRAMA PANEMBAHAN RESO KARYA W.S. RENDRA (SEBUAH ANALISIS SOSIOLOGI SASTRA) - Astri Anggita Aryanti; Asep Firdaus; Fauziah Suparman (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study focuses on the analysis of the form of social criticism contained in the drama Panembahan Reso by W.S. Rendra. The drama Panembahan Reso tells a story about criticism of the New Order government under the leadership of President Soeharto. This study uses a sociology of literature approach and Soerjono Soekanto's sociology of literature theory. The research method used is a qualitative descriptive method. We collected data using reading and recording techniques. Data analysis includes three stages, namely data condensation, data presentation, and drawing conclusions/verification. The results of this study contain forms of social criticism in the form of poverty, crime, family disorganization, and bureaucracy. Social criticism of poverty includes economic problems. Crime criticism includes problems of murder, betrayal, and overthrow of power. Social criticism of family disorganization includes divisions that occur in families. Bureaucratic criticism includes problems of corruption, collusion, and nepotism.